Religious Harmony in India: A Study of the Approach of Maulana Wahiduddin Khan - U Din Mir., Mehraj (International Journal of Psychosocial Rehabilitation, 2019)
This research paper delves into the concept of religious harmony in India, focusing on the approach advocated by Maulana Wahiduddin Khan, a renowned Islamic scholar and thinker. The paper examines Khan’s distinctive strategies for fostering interfaith dialogue and understanding in the context of India’s religious diversity. It analyzes his principles, such as reinterpreting religious texts, emphasizing shared ethical values, promoting non-violence, advocating personal transformation, and facilitating interfaith dialogues. Through a review of Khan’s efforts and initiatives, including the establishment of the Centre for Peace and Spirituality, participation in campaigns for non-violence, engagement in interfaith dialogues and promotion of inclusive education, the paper highlights his lasting impact on Indian society. The research underscores the importance of his teachings in contributing to reduced tensions and improved relations among religious communities, ultimately advocating for a more harmonious and inclusive society.